E-Voting Ketua Osis Di Sekolah SMK Negeri 1 Kepahiang Berbasis Android - Sapri Sapri; Dian Mardiati Sari; Dimas Aulia Trianggara; Heti Heti; Bening Poyemi (Jurnal Dehasen Untuk Negeri, 2023)
Android is one of the most widely used operating systems today. Android-based smartphones really help users in carrying out various activities such as online shopping, communicating, presentations, and many more. Android is a Linux-based operating system. The advantage of Android compared to other mobile phone or smartphone operating systems is that Android is open source code making it easier for developers to create and modify applications or features that do not yet exist on the Android operating system according to their own wishes such as E-Voting for Osis Chairs at SMK schools. Android-based Negeri 1 Kepahiang will implement a system call to get information besides E-Voting for Osis Chairs at the Android-based SMK Negeri 1 Kepahiang school, one of the systematic activities in managing student councilFaster and more focused and on time.